2003
DOI: 10.1007/s12022-003-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of somatostatin receptor subtypes in “clinically nonfunctioning” pituitary adenomas

Abstract: Pituitary tumors diagnosed before surgery as "non-functioning" in fact represent a heterogenous group, the majority of which express glycoprotein hormones or their free subunits. It is known that some of them expresses somatostatin receptors, but the data available until now rarely refer to the receptor subtype. Five different subtypes of somatostatin receptors (sst1-5) have been cloned. We studied 18 pituitary tumors diagnosed before surgery as "non-functioning." After the surgery the tumors were immunostaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
(26 reference statements)
1
14
1
Order By: Relevance
“…Using polyclonal anti-SSTRs antibodies, Pawlikowski et al (2003) reported high expression of SSTR1, SSTR2, and SSTR5, with only little or no expression of SSTR3 in 13 GPAs and five null cell adenomas. The same group later found SSTR3 to be the most commonly expressed subtype in GPAs, followed by SSTR2, with no expression of SSTR5 (Pisarek et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using polyclonal anti-SSTRs antibodies, Pawlikowski et al (2003) reported high expression of SSTR1, SSTR2, and SSTR5, with only little or no expression of SSTR3 in 13 GPAs and five null cell adenomas. The same group later found SSTR3 to be the most commonly expressed subtype in GPAs, followed by SSTR2, with no expression of SSTR5 (Pisarek et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessing expression of SSTR2 in GPAs have produced conflicting results (Pawlikowski et al 2003, Pisarek et al 2009, Ramirez et al 2012. Therefore, we aimed to determine the expression profile of SSTR2, SSTR3, and SSTR5 in a large and homogeneous cohort of patients with primary or recurrent GPAs.…”
mentioning
confidence: 94%
“…Indeed, almost all human tumors express SSTR1 mRNA (Patel 1997), suggesting that compounds also targeting SSTR1, such as pasireotide, might represent a good tool for the control of neoplastic growth. Moreover, an immunohistochemical study demonstrated that SSTR1 is one of the most expressed SSTR subtypes in NFA (Pawlikowski et al 2003). Therefore, stable SRIF analogs binding with high affinity to SSTR1, whether selectively or together with other SSTR subtypes, may indeed open a new frontier in the treatment of NFA.…”
Section: Discussionmentioning
confidence: 99%
“…As far as secondary therapy (i.e. therapy applied after the surgical intervention) is concerned, the use of somatostatin analogues (SSA) is proposed, considering the presence of somatostatin receptors (SSTR) in NFPA [5,6]. Receptor scintigraphy and possibly immunohistochemistry should be performed for the purpose of SSTR detection [7].…”
Section: Introductionmentioning
confidence: 99%